The Impact of BK Channels on Cellular Excitability Depends on their Subcellular Location - Bock, Tobias; Stuart, Greg J. (Frontiers in Cellular Neuroscience, 2016)
Large conductance calcium-activated potassium channels (or BK channels) fulfil a multitude of roles in the central nervous system. At the soma of many neuronal cell types they control the speed of action potential repolarization and therefore they can have an impact on neuronal excitability. Due to their presence in nerve terminals they also regulate transmitter release. BK channels have also been shown to be present in the dendrites of some neurons where they can regulate the magnitude and duration of dendritic spikes. Here, we investigate the impact of modulating the activation of BK channels at different locations on the cellular excitability of cortical layer 5 pyramidal neurons. We find that while somatic BK channels help to repolarize action potentials at the soma and mediate the fast after-hyperpolarisation, dendritic BK channels are responsible for repolarisation of dendritic calcium spikes and thereby regulate somatic action potential burst firing. We found no evidence for a role of dendritic BK channels in the regulation of backpropagating action potential amplitude or duration. These experiments highlight the diverse roles of BK channels in regulating neuronal excitability and indicate that their functional impact depends on their subcellular location.